Dechema chemistry data series : vapor liquid equilibrium data collection 4a ethers (supplement 1) - Gmehling, J.; Onken, U.; Rarey, J.R. (Frankfurt Dechema, 1996)
part 4a
Keywords: Vapor-Liquid equilibrium; Binary Mixtures -- Data tables and diagrams; Ethers